Traffic problems: inherited disease and intracellular trafficking defect - Gissen, Paul (Henry Stewart Talks, 2015)
Concepts and pathways in intracellular trafficking, Disorders affecting specific trafficking steps, Arthrogryposis-Renal dysfunction-Cholestasis (ARC) syndrome, ARC syndrome as an example of a trafficking disorder